Papillary muscle ventricular ectopy ablation in a malignant mitral valve prolapse: Ablation in Malignant Mitral Valve Prolapse. Issue 3 (31st January 2023) - Conti, Sergio; Sabatino, Francesco; Caserta, Carlo; Sgarito, Giuseppe
Abstract: Patients with mitral valve prolapse (MVP) have a heterogeneous clinical spectrum, ranging from benign to severe clinical presentations such as sudden cardiac death (SCD). Some of the markers of "arrhythmic MVP" include inverted/biphasic T‐waves, QT prolongation, and polymorphic premature ventricular contractions (PVCs) originating from the left ventricular outflow tract and papillary muscles (PMs). The genesis of arrhythmias in MVP recognizes the combination of the substrate (fibrosis) and the trigger (mechanical stretch). Therefore, ablation of ventricular arrhythmias originating from PMs in a patient with MVP can be considered an adjunctive strategy to lower the arrhythmic burden and reduce the risk of ICD shocks.